Formulation and evaluation of herbal sunscreen cream - P, Chandini; S, Naga subrahmanyam; Navuduri, Suvarna Jyothi (International Journal of Indigenous Herbs and Drugs, 2025)
Herbal sunscreens provide a safe, natural, and effective alternative to chemical-based products. This study developed a herbal sunscreen cream using blue pea flowers (Clitoria ternatea), coconut oil, rose water, and aloe vera-ingredients known for antioxidant, anti-inflammatory, moisturizing, and healing benefits. These botanicals not only protect against UVA and UVB radiation but also enhance skin defense and repair. Clitoria ternatea, with its strong antioxidant and UV-protective properties, served as the key component. The formulation was evaluated for SPF, pH, viscosity, spreadability, stability, and skin irritation, showing favorable results with good stability and no adverse effects. Overall, the study demonstrates that Clitoria ternatea-based sunscreen is an effective, skin-friendly, and eco-conscious alternative to synthetic sunscreens.